2016
DOI: 10.1111/asj.12652
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the stockperson's attitudes and dairy productivity in Japan

Abstract: The aim of this study is to identify the factors that comprise farmer attitudes toward dairy cows and jobs in Japan, and examine the relationship between these attitudes and dairy productivity. At first, we executed a questionnaire survey to determine factors that comprise attitudes of farmers toward their jobs and dairy cows, and three factors were extracted. These were named as 'Positive beliefs to cows', 'Negative beliefs to cows' and 'Job satisfaction', respectively. Second, we examined the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…In our study, handlers that generally had positive attitude and empathy scores were associated with a significant decrease in the number of negative tactile interactions, such as prodding and shouting; results that coincided with those reported by other researchers in studies on dairy farms [36,37] and extensive beef cattle systems [8]. Likewise, a study evaluating the attitudes of Japanese workers toward cows found that handlers with high positive attitude scores had a greater tendency to exhibit more positive tactile behavior (e.g., petting), and less to encourage and implement effective methods for improving attitudes, such as providing livestock handlers with new information, creating stimuli, constantly reinforcing the need to treat the animals well [8,38], and promoting actions that increase job satisfaction [39], among others.…”
Section: Relationships Between Attitude Empathy and Human-animal Intsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, handlers that generally had positive attitude and empathy scores were associated with a significant decrease in the number of negative tactile interactions, such as prodding and shouting; results that coincided with those reported by other researchers in studies on dairy farms [36,37] and extensive beef cattle systems [8]. Likewise, a study evaluating the attitudes of Japanese workers toward cows found that handlers with high positive attitude scores had a greater tendency to exhibit more positive tactile behavior (e.g., petting), and less to encourage and implement effective methods for improving attitudes, such as providing livestock handlers with new information, creating stimuli, constantly reinforcing the need to treat the animals well [8,38], and promoting actions that increase job satisfaction [39], among others.…”
Section: Relationships Between Attitude Empathy and Human-animal Intsupporting
confidence: 91%
“…In accordance with a psychological perspective, empathy is referred to as the capacity to understand and share the feelings of others, i.e. conspecific negative tactile behavior (e.g., hitting) when handling their animals [37]. In this respect, we observed that the livestock handlers that had negative beliefs and ideas about animals were more likely to behave negatively with them.…”
Section: Relationships Between Attitude Empathy and Human-animal Intsupporting
confidence: 67%
“…Principal components analysis was the most common procedure for condensing attitude items (52%; n = 13), followed by summing single item scores to calculate a final attitude score (16%; n = 4). Other papers used procedures such as factor analysis (Vande Velde et al, 2015;Fukasawa et al, 2017), structural equation measurement models (Toma et al, 2013;Toma et al, 2015), or transforming a 5-point Likert scale into a dichotomous outcome (Kielland et al, 2010).…”
Section: Spectrum Of Studies On Personality and Attitude As Risk Factorsmentioning
confidence: 99%
“…Research studies clearly show the benefits of good stockmanship. Fearful animals with large flight zones that avoid people are less productive [ 19 , 20 , 21 ]. During the last 10 years, the use of training programs to improve stockmanship has increased.…”
Section: Importance Of Stockmanshipmentioning
confidence: 99%